2022
DOI: 10.1136/bmjgast-2022-000913
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Liver Index is a valid predictor of non-alcoholic fatty liver disease (NAFLD) in pregnancy

Abstract: BackgroundDespite the evidence for adverse pregnancy outcomes, non-alcoholic fatty liver disease (NAFLD) is not routinely addressed in early pregnancy. The Fatty Liver Index (FLI) has been proposed as a screening tool for NAFLD in the general population. We aim to develop mathematical models for predicting NAFLD in pregnancy and validate the FLI for first-trimester pregnant women.MethodsBiochemical and biophysical parameters were analysed in pregnant women with period of gestation <12 weeks was done among R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Additionally, a mathematical model provides a standardized framework to monitor disease progression and response to treatment over time. By quantifying grayscale levels, it becomes possible to detect subtle variations and track even small changes in NAFLD, allowing for early intervention and management (15). Moreover, a mathematical model enables researchers and clinicians to investigate potential correlations between grayscale levels and various clinical outcomes, facilitating a deeper understanding of the disease and potentially leading to the identi cation of novel prognostic markers or treatment targets.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a mathematical model provides a standardized framework to monitor disease progression and response to treatment over time. By quantifying grayscale levels, it becomes possible to detect subtle variations and track even small changes in NAFLD, allowing for early intervention and management (15). Moreover, a mathematical model enables researchers and clinicians to investigate potential correlations between grayscale levels and various clinical outcomes, facilitating a deeper understanding of the disease and potentially leading to the identi cation of novel prognostic markers or treatment targets.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 , 13 ] However, challenges remain in determining the ideal method to diagnose NAFLD in the context of pregnancy, given that many tools utilized in non-pregnant individuals have not been validated in pregnancy. [ 14 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] However, challenges remain in determining the ideal method to diagnose NAFLD in the context of pregnancy, given that many tools utilized in non-pregnant individuals have not been validated in pregnancy. [14][15][16] Our study has several unique strengths. First, data were obtained from screening consecutive L&D admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty liver index (FLI) is a surrogate marker of hepatic steatosis, which is estimated from a formula that includes waist circumference (WC), body mass index (BMI), gamma-glutamyltransferase (GGT), and triglycerides (TG) [ 12 ]. This index could replace ultrasonography to diagnose the extent of hepatic steatosis and is a valid predictor of NAFLD [ 13 ]. Several studies have previously observed that FLI was a predictor of diabetes development [ 5 , 13 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This index could replace ultrasonography to diagnose the extent of hepatic steatosis and is a valid predictor of NAFLD [ 13 ]. Several studies have previously observed that FLI was a predictor of diabetes development [ 5 , 13 16 ]. A meta-analysis [ 16 ] identified a positive association between FLI and the risk of diabetes mellitus incidence.…”
Section: Introductionmentioning
confidence: 99%